Relapse of multiple myeloma presenting as extramedullaryplasmacytoma surrounding the aorta: A rare case report - Ekinci, Ömer; Dogan, Ali Nazmi Can; Aslan, Mehmet; Ebinç, Senar; Demir, Cengiz (My University, 2020)
Multiple myeloma (MM) is a hematological disease characterized by the malignant proliferation of plasma cells. MM can be concomitant with plasmacytoma, at diagnosis or during relapse. Extramedullary plasmacytoma (EMP) is rare and is encountered most frequently in the upper respiratory tract and nasopharynx. It is of much less frequent occurrence in the intraabdominal and thoracic regions. EMPs tend to have a poor prognosis with a characteristic of high relapse/refractory disease rates and a relatively short overall survival, despite the use of various novel medications. Here, we present a case of relapse of MM concomitant with a large EMP surrounding the aorta, which is an extremely rare pattern of involvement. Our case showed nearly complete remission with an aggressive chemotherapy regimen. MR imaging served as a guidepost in both the diagnosis and the post-treatment follow-up.
Keywords: Genel ve Dahili Tıp; Hematoloji